Ethical issues in neonatal intensive care - Marcello M. Orzalesi; Marina Cuttini (Istituto Superiore di Sanità, 2011)
Recent progress in neonatal care have significantly improved the prognosis and chances of survival of critically ill or extremely preterm neonates and have modified the limits of viability. However, in some circumstances, when the child's death can only be briefly postponed at the price of severe suffering, or when survival is associated with severe disabilities and an intolerable life for the child and his/her parents, the application of the full armamentarium of modern neonatal intensive care may not be appropriate. In such circumstances the limitation of intensive treatments (withholding or withdrawing) and shift towards palliative care, can represent a more humane and reasonable alternative. This article examines and discusses the ethical principles underlying such difficult decisions, the most frequent situations in which these decisions may be considered, the role of parents in the decisional process, and the opinions and behaviours of neonatologists of several European neonatal intensive units as reported by the EURONIC study.